Contractual Incompleteness, Unemployment, and Labour Market Segmentation. (23rd October 2013) - Altmann, Steffen; Falk, Armin; Grunewald, Andreas; Huffman, David
Abstract: This article provides evidence that involuntary unemployment, and the segmentation of labour markets into firms offering "good" and "bad" jobs, may both arise as a consequence of contractual incompleteness. We provide a simple model that illustrates how unemployment and market segmentation may jointly emerge as part of a market equilibrium in environments where work effort is not third-party verifiable. Using experimental labour markets that differ only in the verifiability of effort, we demonstrate empirically that contractual incompleteness can cause unemployment and segmentation. Our data are also consistent with the key channels through which the model explains the emergence of both phenomena.